Pembaharuan Regulasi Perlindungan Konsumen Terhadap Risiko dan Manfaat Artificial Intelligence - Suratno Suratno; Yuniwati Yuniwati; Zulfikar Ali; Dewi Noviyanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The need for regulations that can protect consumers in business in the digital era is increasingly urgent along with the use of AI. However, the consumer protection regulations currently owned by Indonesia were set long before the digital era, so they are not adequate in protecting consumers in the era of AI utilization. Therefore, this article aims to analyze the current consumer protection legal regime in Indonesia and understand the update of consumer protection regulations in the application of AI. The research method used is normative juridical supported by a legal approach and a case approach. The analysis method used in this study is descriptive-qualitative analysis. The results of the study show that regulations in the field of consumer protection in Indonesia are currently inadequate in protecting consumer interests in the era of AI utilization. Therefore, it is necessary to update consumer protection regulations, especially related to the application of AI in the business sector, which is able to accommodate the complexity of consumer protection in the digital era. The regulatory update is intended to protect consumers and not to limit innovation in AI development.